Sudan Famine Crisis in International Media - Nurhidayah, Elva; Basid, Abdul (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The Sudan crisis is an important topic that reflects global humanitarian challenges, yet there is a gap in the literature regarding media representations of this issue. This study aims to uncover how two media outlets, royanews.tv and Aljazeera, portray the famine crisis in Sudan, with a focus on the role of the United States and its geopolitical impact. The method used is a qualitative descriptive approach, with data collection techniques through text analysis of two news reports. The main findings show that the media plays a significant role in shaping public perceptions by using attention-grabbing terms such as "humanitarian catastrophe." The resulting discourse reflects power relations, where media narratives can benefit or harm certain actors in the existing political context. In addition, there are hidden ideologies in the use of language that support or challenge power, in line with Critical Discourse Analysis (CDA) theory. The conclusion of this study confirms that language in media discourse not only shapes public perception, but also reflects and maintains power relations, and influences social and political narratives. This research demonstrates the important role of the media in international responses to humanitarian crises.